Electoral cycles in savings bank lending - Till Stowasser; Florian Englmaier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We provide causal evidence that German savings banks where local politicians are by law involved in their management systematically adjust lending policies in response to local electoral cycles. The different timing of county elections across states and the existence of a control group of cooperative banks that are very similar to savings banks but lack their political connectedness allow for clean identification of causal effects of county elections on savings banks lending. These effects are economically meaningful and robust to various specifications. Moreover, politically induced lending increases in incumbent party entrenchment and in the contestedness of upcoming elections.
Keywords: D72; D73; G21; 330